Legal Analysis of Providing Documents by a Notary to People Who Have No Direct Interest (MA Case Study Number 20/PK/PID/2020) - Maulia Permata Rizki Pohan; Suprayitno; Sutiarnoto; Abdul Harris (JUSTICES: Journal of Law, 2024)
This study aims to determine and analyze the concept of UUJN and Legislation related to the obligation of notaries in providing documents to direct interested persons. To determine and analyze the sanctions for notaries who make power of sale deeds without the support of valid proof of ownership. To find out and analyze the legal protection of good faith buyers for the negligence of notaries who provide certificates to unauthorized parties Decision Number 20 PK/PID/2020. First, the conclusion states that every unlawful act that brings harm to another person, obliges the person who through his fault causes the loss, to compensate for the loss and everyone is responsible not only for losses caused by his actions, but also for losses caused by his negligence or lack of caution. Second, the legal consequences or sanctions for notaries who make power of sale deeds without valid proof of ownership can be subject to administrative sanctions in the form of written warnings, temporary dismissal, respectful dismissal, or dishonorable dismissal. Notaries may also be subject to civil sanctions. Third, the legal protection of good faith buyers against the negligence of notaries who provide certificates to unauthorized parties in Decision Number 20 PK/PID/2020. In principle, the law always provides legal protection to good faith buyers.